2019
DOI: 10.1016/j.mayocp.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Relationship Between Atrial Fibrillation, Multimorbidity and Oral Anticoagulant Drug Use

Abstract: Manuscript Word Count: 3210 Tables: 3 Figures: 2 References: 36 FUNDING No funding was provided for this project. DISCLOSURES MP reports consultant activity for Boehringer Ingelheim. PMM reports honoraria for lectures as speaker or chair symposia organized by Bayer, Grifols, Kedrion, LFB, Novo Nordisk and Pfizer; scientific consultant for Bayer, Baxalta and Kedrion. GB reports small speaker's fee from Medtronic, Boston, Boehringer and Bayer. GYHL reports consultant activity for Bayer/Janssen, BMS/Pfizer, Biotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 37 publications
4
60
0
2
Order By: Relevance
“…Vulnerable older AF patients are frequently characterized by multimorbidity, polypharmacy, increased falling risk, frailty and dementia ( Jaspers Focks et al., 2016 ; Piccini et al., 2016 ; Steffel et al., 2016 ; Martinez et al., 2018 ; Rao et al., 2018 ; Alexander et al., 2019 ). Consequently, OACs tend to be inappropriately underdosed or discontinued in these patients subgroups ( Viscogliosi et al., 2017 ; Oqab et al., 2018 ; Madhavan et al., 2019 ; Proietti et al., 2019 ; Besford et al., 2020 ; Kapoor et al., 2020 ; Sanghai et al., 2020 ). However, even in AF patients ≥90 years old ( Raposeiras-Roubín et al., 2020 ), at high risk of falling ( Man-Son-Hing et al., 1999 ) or with dementia ( Orkaby et al., 2017 ; Subic et al., 2018 ), OAC continuation was still beneficial compared to omitting the OAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vulnerable older AF patients are frequently characterized by multimorbidity, polypharmacy, increased falling risk, frailty and dementia ( Jaspers Focks et al., 2016 ; Piccini et al., 2016 ; Steffel et al., 2016 ; Martinez et al., 2018 ; Rao et al., 2018 ; Alexander et al., 2019 ). Consequently, OACs tend to be inappropriately underdosed or discontinued in these patients subgroups ( Viscogliosi et al., 2017 ; Oqab et al., 2018 ; Madhavan et al., 2019 ; Proietti et al., 2019 ; Besford et al., 2020 ; Kapoor et al., 2020 ; Sanghai et al., 2020 ). However, even in AF patients ≥90 years old ( Raposeiras-Roubín et al., 2020 ), at high risk of falling ( Man-Son-Hing et al., 1999 ) or with dementia ( Orkaby et al., 2017 ; Subic et al., 2018 ), OAC continuation was still beneficial compared to omitting the OAC.…”
Section: Discussionmentioning
confidence: 99%
“…However, concerns have risen regarding the effectiveness and safety of NOACs in real-life clinical practice in patients with multiple comorbidities and concomitant medication use, especially vulnerable geriatric patients with AF who were largely underrepresented in these trials ( Lee et al., 2012 ). Consequently, NOACs tend to be underused or underdosed in these patients due to concerns of excessive fall-related intracranial bleeding, cognitive impairment with suboptimal therapy adherence, multiple drug-drug interactions (DDIs), low body weight or impaired renal function ( Viscogliosi et al., 2017 ; Oqab et al., 2018 ; Proietti et al., 2019 ; Madhavan et al., 2019 ; Besford et al., 2020 ; Kapoor et al., 2020 ; Sanghai et al., 2020 ). Therefore, there is an urgent need for a critical appraisal of the added value of NOACs in geriatric patients with AF at high thromboembolic and bleeding risk.…”
Section: Introductionmentioning
confidence: 99%
“…In view of its epidemiological profile, AF affects subjects in the range of age at highest risk of adverse outcomes if infected by Sars-Cov-2 [33] and the caution in avoiding admissions to hospital may explain the important reduction in acute pharmacological and non-pharmacological treatments applied for AF in emergency setting reported during the study period, as reported in this survey. Since appropriate prescription of oral anticoagulants in patients at risk of stroke is a major determinant of outcome at long term [34][35][36][37][38][39][40], it will be necessary in the near future to establish even stricter connections between hospital and out of hospital care, for a re-assessment of patients who presented AF and these months with regard to clinical evaluation and appropriateness of treatment for ensuring continuity of care. It will also be interesting to assess to what extent untreated or undiscovered AF occurred during the lockdown will result in major consequences, such as syncope, heart failure, stroke/systemic embolism [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…We note that the high levels of anticoagulant prescribing that we observed are against a background of multi-morbidity, which would be expected to increase the potential iatrogenic effects of anticoagulation prescribing, as multi-morbidity increases risk of haemorrhage. 22…”
Section: Discussionmentioning
confidence: 99%